Role of clouds in accelerating cold‐season warming during 2000–2015 over the Tibetan Plateau - Shan Hua; Yuzhi Liu; Rui Jia; Shuting Chang; Chuqiao Wu; Qingzhe Zhu; Tianbin Shao; Bing Wang (International Journal of Climatology, 2018)
With the global warming slowdown in the twenty‐first century, a huge discrepancy in regional climate warming has been identified over the main region of the Tibetan Plateau (TP). Compared with the +0.04 °C/decade warming from 1961 to 1999, the warming greatly accelerated for the period 2000–2015 at a rate of +0.30 °C/decade. During the same period, warming in the cold season (November to March) was more pronounced than in the warm season (May to September) over the TP. The results also indicated that the middle‐level cloud (middle cloud) decreased (−0.359%/year), while the high‐level cloud (high cloud) increased (+0.241%/year) over almost all the TP during the cold season. Further analysis showed positive net cloud radiative forcing over the western TP from 2000–2015, that is, a heating effect of clouds, especially in the cold season. Combining the trends of the increase in high cloud and the decrease in middle cloud over most parts of the TP, the decreased albedo effect of middle cloud and the increased longwave greenhouse effect of high cloud may have partially contributed to the sustained warming, especially in the cold season from 2000 to 2015. Meanwhile, the results showed that the warming rate and cloud area fraction changes were significantly amplified with elevation. The analysis based on a model of Coupled Model Intercomparison Project Phase 5 shows that the decreased middle cloud plays more important role than the increased high cloud in modulating the enhanced warming over the TP, especially in the cold season.